Vth International Congress of the latin group of physical medicine and sports (Fiep Bulletin - online, 2015)
Announces in detail in Nos. 1-2 and 3,1965, of this Bulletin, the Congress took place from the 13th to the 17th September 1965,in the magnificent halls of the ritz hotel, in Lisbon.